Bagaimana motivasi kerja Islam memoderasi pengaruh lingkungan kerja, pengalaman kerja, dan reward terhadap kinerja karyawan? - Yunus, Muhammad; Mochlasin, Mochlasin (Journal of Management and Digital Business, 2022)
This study aimed to analyze the influence of the work environment, work experience, and rewards on the performance of employees with Islamic work motivation as a moderating variable for BTN Syariah KC Surakarta employees. The sampling method used is a saturated sample by making the entire population a research sample. The sample of this study was 54 BTN Syariah KC Surakarta employees. Statistical analysis technique using moderated regression analysis. The results of this study state that the work environment does not affect employee performance, while work experience and rewards have a positive and significant effect on employee performance. The Islamic work motivation variable cannot strengthen the influence of the work environment, work experience, and rewards on employee performance.